Exploring the dual nature of supplier relationship commitment on buyer behaviors: Considering the levels of buyer-leverage. Issue 2 (17th December 2019) - Verghese, Anto John; Koufteros, Xenophon; Peters, Richard
Abstract : Purpose: The authors argue that the supplier's perspective in managing buyers using relationship commitment is incomplete. The primary reasons for incompleteness are that: the effects of the two types of relationship commitment (i.e. affective and continuance) on buyer behaviors (i.e. individualized consideration and opportunism) are largely ignored from a supplier's perspective; there is quandary regarding the effects of the two relationship commitment types in a relationship, whether they are favorable or not; and there is also ambiguity regarding the conditions under which relationship commitment types might serve as effective relational governance mechanisms. The paper aims to discuss this issue. Design/methodology/approach: The authors employ survey data obtained from 207 suppliers to test the hypotheses using structural equations modeling. Findings: The authors extend contemporary knowledge on supplier relationship commitment by revealing that at high-levels of buyer-leverage, supplier affective commitment can induce buyer opportunism and supplier continuance commitment can induce buyer individualized consideration. Furthermore, buyer-leverage positively moderates the interaction effect of supplier commitment types to promote buyer opportunism. Research limitations/implications: The authors do not examine a buyer's perspective, but from a supplier's perspective, suppliers can maximize their benefits from their relationship commitment by embracing affective commitment while ensuring that buyers do not have excessive leverage. Originality/value: The study presents a significant contribution to the extant literature on relationship commitment by probing the dual nature of supplier relationship commitment; albeit for specific configurations of commitment types and buyer-leverage.